2014
DOI: 10.1128/jcm.02868-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Genotypic Relation, and Clinical Features of Colistin-Resistant Isolates of Acinetobacter Genomic Species 13BJ/14TU from Bloodstreams of Patients in a University Hospital

Abstract: Colistin resistance remains rare among clinical isolates of Acinetobacter species. We noted the emergence of colistin-resistant bloodstream isolates of the Acinetobacter genomic species (GS) 13BJ/14TU from patients at a university hospital between 2003 and 2011. We report here, for the first time, the microbiological and molecular characteristics of these isolates, with clinical features of Acinetobacter GS 13BJ/14TU bacteremia. All 11 available patient isolates were correctly identified as Acinetobacter GS 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…These strains were isolated from patients who had never received colistin treatment, suggesting that the strains were intrinsically resistant to colistin (18,19). These isolates were distinguished from the A. baumannii complex and are now classified as Acinetobacter GS 13BJ/14TU, based on partial nucleotide sequence homology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These strains were isolated from patients who had never received colistin treatment, suggesting that the strains were intrinsically resistant to colistin (18,19). These isolates were distinguished from the A. baumannii complex and are now classified as Acinetobacter GS 13BJ/14TU, based on partial nucleotide sequence homology.…”
Section: Discussionmentioning
confidence: 99%
“…A nucleotide sequence analysis is a reliable method for discriminating between minor species, but it is difficult to perform in a routine laboratory setting. Nonetheless, it should be considered in cases of isolates with atypical drug susceptibility patterns or in patients with specific clinical backgrounds (18,23).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Acinetobacter genomic species 13BJ/14TU had not been correctly identified using some phenotypic identification systems and the VitekMS matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) microbial identification system, although correct identification was achieved using partial rpoB gene sequencing (4,8). In the present study, we showed that Acinetobacter genomic species 13BJ/14TU can be reliably differentiated from other Acinetobacter species using MALDI-TOF mass spectrometry (MS).…”
mentioning
confidence: 75%
“…Later studies suggested that these two taxa were congruent with each other at the species level and represented a distinct phylogroup within the hemolytic-proteolytic clade of the genus Acinetobacter (3). Reports from different countries showed that strains of Acinetobacter genomic species 13BJ/14TU were found in clinical specimens at a frequency similar to or even higher than that of another hemolytic and proteolytic species, Acinetobacter haemolyticus (4)(5)(6). It has also been noted that strains of Acinetobacter genomic species 13BJ/14TU are intrinsically resistant to polymyxins (4,7), which further underpins the clinical relevance of this taxon.…”
mentioning
confidence: 99%
“…34 Although colistin resistance has been reported, it remains an infrequent occurrence. 35 The most commonly used therapies for multidrug-resistant or XDR Acinetobacter spp include high-dose ampicillin/sulbactam, tigecycline, and colistin. It is unclear whether there is a benefit from combination therapy compared with monotherapy, but carbapenems, aminoglycosides, and rifampicins have been used as adjunctive therapy.…”
Section: Gram-negative Infectionsmentioning
confidence: 99%